The Effect of Financial Compensation & Non-financial Compensation on Employee Performance at PT Pelabuhan Indonesia III (Persero) East Java Region - Eva Maya Sabatini; Bayu Airlangga Putra; Hermien Tridayanti; Elok Damayanti (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
The purpose of this study was to analyze the partial effect of financial compensation and non-financial compensation on employee performance at PT Pelabuhan Indonesia III (Persero) Regional East Java. This study explains the effect of financial and non-financial compensation on employee performance at PT Pelabuhan Indonesia II (Persero) Regional East Java using data from questionnaire results. In this study, the population used was the employees of the PT Pelabuhan Indonesia III company, with the research sample set as many as 67 respondents, namely employees of PT Pelabuhan Indonesia III. The analysis employed was the multiple linear regression analysis. Multiple linear regression analysis can be used to analyze the effect of independent variables (financial and non-financial compensation) on employee performance as the dependent variable. Based on the analysis of the research results, it can be concluded as follows: Financial Compensation has a positive and partially significant effect on the Employee Performance of PT Pelabuhan Indonesia III (Persero) Regional East Java; Non-financial compensation has a positive and significant effect partially on the performance of employees of PT Pelabuhan Indonesia III (Persero) East Java Region; Financial Compensation and Non-financial Compensation have a positive and significant simultaneously on the Performance of Employees of PT Pelabuhan Indonesia III (Persero) East Java Region.